Pesticide Exposure and Its Correlation with Hemoglobin and Cholinesterase in Farmers Who Used Pesticide - Arum Nuryati; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, 2022)
Background: Agriculture is the most important sector in basic human needs. Farmers must improve the quality of agricultural products by using synthetic chemicals, someone who experiences pesticide poisoning will have low cholinesterase levels. This study aims to analyze pesticide exposure to hemoglobin and cholinesterase levels in farmers who use pesticides.Subjects and Method: This was a systematic review study and meta-analysis conducted with the PRISMA diagram guidelines. The search for articles was carried out taking into account the eligibility criteria defined in the PICO model. Population= farmers using pesticides, Intervention= exposed to pesticides, Comparison= not exposed to pesticides, Outcome= hemoglobin and cholinesterase levels. The article search process was carried out between 2002-2022 from the Pubmed, Science Direct, Google Scholar, Springer Link, Hindawi, and Plose one databases. The keywords used were “hemoglobin”, “exposed pesticide”, “cholinesterase level”, “farmers”, “hemoglobin AND exposed pesticide”, “cholinesterase level AND farmers”, “hemoglobin AND farmers”. The inclusion criteria in this study were the full text of a cross-sectional study, discussing pesticide exposure to hemoglobin and cholinesterase levels in farmers using pesticides, published in English. Final results are presented in the mean SD of the multivariate analysis. Data analysis was performed using RevMan 5.4 software.Results: A meta-analysis was conducted on 13 articles originating from America, Asia, Africa, and Europe. The results of the meta-analysis showed that farmers exposed to pesticides experienced a decrease in hemoglobin, but it was not statistically significant (SMD= -0.28; 95% CI= -1.10 to 0.54; p=0.500). Pesticide exposure reduced cholinesterase levels in farmers using pesticides, the results were statistically significant (SMD= -2.48; 95% CI= -3.68 to -1.27; p<0.001).Conclusion: The results of the meta-analysis showed that pesticide exposure decreased hemoglobin and cholinesterase levels in farmers using pesticides. Keywords: hemoglobin, cholinesterase levels, farmers Correspondence:Arum Nuryati. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: arumnuryati@student.uns.ac.id. Mobile: +6285728792097